Investigation of 5’-Norcarbocyclic Nucleoside Analogues as Antiprotozoal and Antibacterial Agents - Khandazhinskaya, Anastasia L. (Molecules, 2019)
Carbocyclic nucleosides have long played a role in antiviral, antiparasitic, and antibacterial therapies. Recent results from our laboratories from two structurally related scaffolds have shown promising activity against both Mycobacterium tuberculosis and several parasitic strains. As a result, a small structure activity relationship study was designed to further probe their activity and potential. Their synthesis and the results of the subsequent biological activity are reported herein.